2020
DOI: 10.3892/etm.2020.9538
|View full text |Cite
|
Sign up to set email alerts
|

miR‑218 inhibits glucose metabolism in non‑small cell lung cancer via the NF‑κB signaling pathway

Abstract: High glucose metabolism is recognized as one of the hallmarks of cancer and increased expression levels of several key factors involved in glucose metabolism have been reported in non-small cell lung cancer (NSCLC). Previous studies showed that microRNA (miR)-218 is reduced in NSCLC, but its function in glucose metabolism in NSCLC is not fully understood. The present study aimed to investigate the effect of miR-218 on glucose metabolism in NSCLC cell lines and the underlying molecular mechanism. The present re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The up-regulation of glycolysis levels has been observed in many cancers, including primary and metastatic cancers, and aerobic glycolysis is the most commonly used and preferred mechanism of glucose metabolism in cancer cells [ 54 ]. Previous studies [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ] showed that signaling pathways such as Akt, Myc, ERK, and NF-κB play an important regulatory role during glycolysis. In NSCLC, high levels of glucose transporter 1 (GLUT1) and hexokinase 2 (HK2) promoted glucose uptake by lung cancer cells, which was the initial step of glucose metabolism [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The up-regulation of glycolysis levels has been observed in many cancers, including primary and metastatic cancers, and aerobic glycolysis is the most commonly used and preferred mechanism of glucose metabolism in cancer cells [ 54 ]. Previous studies [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ] showed that signaling pathways such as Akt, Myc, ERK, and NF-κB play an important regulatory role during glycolysis. In NSCLC, high levels of glucose transporter 1 (GLUT1) and hexokinase 2 (HK2) promoted glucose uptake by lung cancer cells, which was the initial step of glucose metabolism [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors also found that miR-218, which is elevated in DKD, negatively regulates DACH1 (15). Since miR-218 inhibits glucose uptake in cancer (16), it would be interesting to investigate the direct or indirect effects of DACH1 on glucose uptake in renal cells, for example, by regulating SGLT2. Doke et al identified DACH1 as a potential candidate gene in a genetic a positive correlation of DACH1 expression with kidney function and a negative correlation with kidney fibrosis, inflammation, and cell proliferation (13).…”
Section: Dach1 and Renal Tubular Injurymentioning
confidence: 98%
“…Moreover, autophagy inhibitors protect recombinant human arginase (rhArg)-treated NSCLC cells, and thus, rhArg-induced autophagy and apoptosis is anti NSCLC progression [ 172 ]. Through influencing arginine synthesis, Aconiti Radix Cocta (ARC) is suggested to be an anti-tumor by regulating the energy metabolism that influence arginine synthesis [ 173 ].…”
Section: Blocking Common Nsclc Metabolic Pathways As Anti-nsclcmentioning
confidence: 99%